1992
DOI: 10.1007/bf01900712
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of structurally abnormal Y chromosomes

Abstract: SummaryThree probes each detecting a locus on the proximal tong arm of the Y chromosome were partially sequenced. Thus, 3 sets of novel primers were developed which enable PCR detection of these 3 loci. Five previously reported primer sets, 3 on the short arm and each one on the centromere and the distal long arm, were mapped along with the novel three using a mapping panel consisted of 8 patients each with different structural abnormality of the Y chromosome. Now, PCR detection of these 8 loci covering an ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…In addition, two STS's (sY159 and sY160) were amplified by single PCR to determine if the deletions encompassed heterochromatic region at distal Yq. We also used primers specific to PABX and PABY genes to amplify the junction of the Xp and Yp pseudoautosomal region, respectively [Nagafuchi et al, 1992]. All possible deletions detected by multiplex PCR were always confirmed by single PCR.…”
Section: Cytogenetic Studymentioning
confidence: 99%
“…In addition, two STS's (sY159 and sY160) were amplified by single PCR to determine if the deletions encompassed heterochromatic region at distal Yq. We also used primers specific to PABX and PABY genes to amplify the junction of the Xp and Yp pseudoautosomal region, respectively [Nagafuchi et al, 1992]. All possible deletions detected by multiplex PCR were always confirmed by single PCR.…”
Section: Cytogenetic Studymentioning
confidence: 99%
“…The primer sequences and the PCR condition have been reported in Genome Database (GDB), except for those for AMELY which detects X-and Y-speci®c bands concomitantly [Ngafuchi et al, 1992].…”
Section: Pcr Analysis For Yp Locimentioning
confidence: 99%
“…The FISH probes used are cY29 for the Xp/Yp telomeric region [Ning et al, 1996], 34F5 for SHOX [Rao et al, 1997], pHu14 for SRY (Department of Genetics, Cambridge University), an ␣-satellite probe for DYZ3 (Oncor), a cosmid probe for DAZ (SRL), and c8.2/1 for the Xq/Yq telomeric region [Ning et al, 1996]. The PCR primer sequences for AMELY have been described in Nagafuchi et al [1992], and those for the remaining loci have been reported in Genome Database. DNA of the patient and the parents (Fig.…”
Section: Dna Analysismentioning
confidence: 99%